Vibration Test Fixtures Design for Payload of Tubular Telemetry System - Muksin, Muksin; Pratama, Mikhael Gilang Pribadi P.; Nugroho, Yudha Agung; Wijaya, Yusuf Giri; Ula, Nur Mufidatul; Wirawan, Adi (Jurnal ILMU DASAR, 2022)
Vibration testing on telemetry system payload is needed to determine its resistance to vibration during operation. Vibration testing of telemetry system payloads requires a test fixture. Test fixture is used to transmit vibration from shaker to telemetry system payload. The payload of telemetry system to be tested is a tubular. The test fixture in this study was designed using SolidWorks software. The material used for manufacture of test fixture is aluminum. Aluminum material was chosen because it has good rigidity with a relatively light mass. Stiffness and mass properties affect to natural frequency value of test fixture, which must be greater than the frequency range of operating telemetry system. Data collection uses two accelerometers placed on test fixture. Sine sweep vibrations are given from 5 Hz to 2000 Hz with a constant amplitude of 1 g and a sweep rate of 1 octave/minute. The test produces three peaks that they are candidates as natural frequencies, i.e at a frequency of 1532 Hz with an amplitude of 2.898 g, a frequency of 1706 Hz with an amplitude of 6.582 g, and at a frequency of 1806 Hz with an amplitude of 6.472 g. From those three natural frequencies, the second natural frequency at 1706 Hz is the most critically because it has the largest response value.